2016
DOI: 10.1039/c6ra06422a
|View full text |Cite
|
Sign up to set email alerts
|

Tuning α-Fe2O3 nanotube arrays for the oxygen reduction reaction in alkaline media

Abstract: α-Fe2O3 nanotube arrays were fabricated and employed as low cost non-noble electrocatalysts for the oxygen reduction reaction (ORR). As-prepared α-Fe2O3 nanotube arrays exhibit excellent ORR catalytic activity and durability in alkaline media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 50 publications
(52 reference statements)
2
15
1
Order By: Relevance
“…When subjected to the codoping process, CNOs increase their activity, as witnessed by the larger electron-transfer number, namely, 3.94. Such a high value is among the largest ever reported for doped C-based materials ,,,,,, and also considering other cost-effective ORR catalysts, , being quite close to that of reference Pt/C and the theoretical one (i.e., 4), as reported in Figure B. These results once again prove that the codoping of CNOs is an effective route to improving their electrochemical activity.…”
Section: Resultssupporting
confidence: 85%
“…When subjected to the codoping process, CNOs increase their activity, as witnessed by the larger electron-transfer number, namely, 3.94. Such a high value is among the largest ever reported for doped C-based materials ,,,,,, and also considering other cost-effective ORR catalysts, , being quite close to that of reference Pt/C and the theoretical one (i.e., 4), as reported in Figure B. These results once again prove that the codoping of CNOs is an effective route to improving their electrochemical activity.…”
Section: Resultssupporting
confidence: 85%
“…However, the incorporation of Cu and Fe resulted in higher current density than the pristine MnO 2 . Compared to previous research of catalysts containing MnO 2 , CuO, and Fe 2 O 3 compounds, it was found that their long‐term electrochemical stability has improved [174–183] …”
Section: Resultscontrasting
confidence: 60%
“…Just to cite some example, Gorlin et al . synthetized Mn 3 O 4 nanoparticles which showed good activity toward the ORR, while Xue and co‐workers fabricated α‐Fe 2 O 3 nanotube arrays characterized by a predominant 4‐electrons pathway, even if applications of iron oxides as ORR catalysts are still very few. Concerning the doped carbonaceous materials, in addition to porous carbon (often employed as support for other most‐performing catalysts), carbon nanotubes, graphite aerogels or graphene/reduced graphene oxide (rGO) were proved to be effective low‐cost catalysts alternative to Pt.…”
Section: Introductionmentioning
confidence: 99%